2016
DOI: 10.1177/0033294116667699
|View full text |Cite
|
Sign up to set email alerts
|

Attention Moderates the Relationship Between Primary Psychopathy and Affective Empathy in Undergraduate Students

Abstract: Psychopathy is personality traits, which is consisted of primary psychopathy characterized by affective and interpersonal problems and secondary psychopathy characterized by behavioral problems. Prior researchers have suggested that people with psychopathy have peculiar attention, which prevents them from detecting information peripheral to their concern, and we hypothesized that this explains their low empathy. Based on these reasoning, the present study assessed whether attention moderates the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
5
0
1
Order By: Relevance
“…Previous studies demonstrated that self-injurious behaviors are related to anxiety, while explanation of this relationship is complicated [ 58 , 59 ]. Individuals with anxiety often adopt a catastrophic cognitive emotion regulation strategy [ 60 ]. Autistic adolescents often have poor skills in emotional regulation, which may lead them to exhibit self-injurious impulsivity [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that self-injurious behaviors are related to anxiety, while explanation of this relationship is complicated [ 58 , 59 ]. Individuals with anxiety often adopt a catastrophic cognitive emotion regulation strategy [ 60 ]. Autistic adolescents often have poor skills in emotional regulation, which may lead them to exhibit self-injurious impulsivity [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our sample, the higher the measure of psychopathic traits, the lower the levels of the total empathy scores, in accordance with our hypothesis. Low empathy has been considered a hallmark feature of psychopathy, and psychopathic individuals usually show deficits in affective responses and emotion cognition (Tamura et al, 2016). Pursuant to the response modulation theory, the solely goal-oriented focus of attention makes them undiscerning to threats or punishment cues (Zeier et al, 2009).…”
Section: Psychopathy Subtypes and Empathymentioning
confidence: 99%
“…Several studies reveal that empathic and affective dysfunction in clinical psychopathy can be generalised to subclinical psychopaths (Seara-Cardoso et al, 2015;Tamura et al, 2016). Early work conducted by Iria and Barbosa (2009) on clinical and nonclinical psychopathic samples finds both groups have significant problems in accurately detecting and discerning facial expressions of fear.…”
Section: Joepp 81mentioning
confidence: 99%
“…Early work conducted by Iria and Barbosa (2009) on clinical and nonclinical psychopathic samples finds both groups have significant problems in accurately detecting and discerning facial expressions of fear. Furthermore, recent work reports on problems for both clinical and subclinical samples with affective but not cognitive empathy (Tamura et al, 2016). This manifests as having little interest in other people and a general failure to feel, identify and lend any importance to emotional events whatsoever.…”
Section: Joepp 81mentioning
confidence: 99%